Revalidation and redescription of Feltia deprivata (Walker) (= bilitura of authors) (Lepidoptera: Noctuidae), a pest species on South America - Blas, Germán San; Agraín, Federico (Zootaxa, 2017)
Agrotis bilitura Guenée (Lepidoptera: Noctuidae) is cited on numerous works as a pest species in South America and as senior synonym of Feltia deprivata (Walker). Previous studies noted that both species were not synonymies, but valid species. The revision of type material of these species allow us to regard both species as valid species belonging to different genera. In the present work, we revalidate F. deprivata, giving a complete description of the morphological characters for male and female adults. As stated on previous works, we also support that A. bilitura belongs within the genus Pseudoleucania Staudinger, proposing the following nomenclatural changes: Pseudoleucania bilitura (Guenée) stat. rev., also lectotypes of Lycophotia atrifascia Hampson were designated in order to definitely provide name-bearing types to the type material studied and to stabilize nomenclature. Finally, we carry out a revision of all the literature concluding that the actual pest species in South America is F. deprivata not P. bilitura, and updating and correcting the distributional and hosts plant information for F. deprivata.